LEARNING MEDIA DEVELOPMENT OF BOARD GAME “THE LABYRINTH OF TRIGONOMETRY” IN TRIGONOMETRY MATERIALS FOR THE 10th GRADE SENIOR HIGH SCHOOL - Tri Nova Hasti Yunianta (Satya Widya, 2018)
Interaction is essential in mathematics learning process, so effective means to promote students’ interaction is compulsory. This research was appointed to develop the board game learning media “The Labyrinth of Trigonometry”, which is adequate to be implemented in trigonometry problem practices. Employing Research and Development (R&D), this research utilized the ADDIE model built of 5 stages, namely: analysis, design, development, implementation, and evaluation. Notably, this board game had been clarified to be a valid learning media by teaching material and media experts, exceptionally obtained 94% and 86% category. 35 students of 11th grade of Senior High School 1 Ambarawa were selected as the participants. The result showed that the practical index obtained excellent category (96%) and the Wilcoxon test significance result was 0.00 (less than 0.05) with higher posttest mean score than pretest. Eventually, the researcher concluded that “The Labyrinth of Trigonometry” was a valid, practical, and effective learning media.